Retrospective analysis of maxillary sinus septa - A cone beam computed tomography study - Ghaida Alhumaidan; Manal Abdalla Eltahir; Safia Shoeb Shaikh (Elsevier, 2021)
Background: Sinus lift procedures have become a routine and reliable way to gain bone volume in the posterior maxilla for implant placement. The presence of an antral septum in the maxillary sinus increases the risk of complications and subsequent implant failure. This study was designed to estimate the prevalence of maxillary sinus septa and its correlation with age, sex, dentition status and the risk of perforating the Schneiderian membrane using cone beam computed tomography (CBCT). Methods: This retrospective, cross-sectional study consisted of a total of 178 CBCT images (100 male, 78 female), 63.0% were dentate, 36.0% partially dentate and 1.1% edentate subjects with a mean age of 35 ± 45 years was analyzed to determine the prevalence, height, location, and orientation of maxillary sinus septa. The septa were classified according to the modified Al-Faraje's classification into VII septal patterns, and the risk of perforation of the Schneiderian membrane was estimated. The chi-square test was used to compare categorical variables, and Student's t-test and the Kruskal-Wallis test were used to compare continuous variables. Results: Septa were present in 25.6% of the sinus segments (37.64% of the subjects). The mean septum height was 5.22 mm ± 2.06 in males and 6.27 mm ± 3.55 in females. The majority of septa were located in the middle 76.92%, while 4.40% were anterior, and 18.68% were posterior; 76.92% were in a buccopalatal direction, whereas 23.08% were in an anteroposterior direction. Class III was the most prevalent type. Overall, 60.4% had a moderate risk of membrane perforation, 30.8% had a low risk, and only 8.8% had a high risk. Conclusion: Three-dimensional CBCT image analyses can be used as a diagnostic tool to provide accurate information that can help avoid unnecessary intra- and postoperative complications during sinus augmentation procedures by identifying the anatomic structures inherent to the maxillary sinus.